2017
DOI: 10.1111/1745-9125.12162
|View full text |Cite
|
Sign up to set email alerts
|

Parenthood as a Turning Point in the Life Course for Male and Female Gang Members: A Study of Within‐individual Changes in Gang Membership and Criminal Behavior

Abstract: The impact of parenthood on leaving a street gang is not well understood. This is likely because researchers in prior studies have not accounted for multiple dimensions of gang exit, possible gender differences, and potential selection bias. In this study, we use a sample of 466 male and 163 female gang members from the National Longitudinal Study of Youth 1997 to consider the within‐individual relationship between changes in parenthood and changes in claiming gang membership and offending. These data offer th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(31 citation statements)
references
References 98 publications
2
28
0
1
Order By: Relevance
“…By understanding racial and ethnic variations in how youth discuss their motivations for leaving the gang, this work will help to build the body of research on racial and ethnic variations in criminal careers over the life course. Additionally, this manuscript will complement recent work that explores factors that facilitate or hinder the gang desistance process such as school transitions and parenthood (Carson et al 2017;Pyrooz et al 2017). Previous research examining trajectories of gang membership has found that minority gang youth tend to stay in a gang for longer periods of time than their white counterparts (Pyrooz 2014;Pyrooz et al 2013), but little is known about why belonging to a racial/ethnic minority group may slow the gang desistance process.…”
Section: Introductionmentioning
confidence: 79%
“…By understanding racial and ethnic variations in how youth discuss their motivations for leaving the gang, this work will help to build the body of research on racial and ethnic variations in criminal careers over the life course. Additionally, this manuscript will complement recent work that explores factors that facilitate or hinder the gang desistance process such as school transitions and parenthood (Carson et al 2017;Pyrooz et al 2017). Previous research examining trajectories of gang membership has found that minority gang youth tend to stay in a gang for longer periods of time than their white counterparts (Pyrooz 2014;Pyrooz et al 2013), but little is known about why belonging to a racial/ethnic minority group may slow the gang desistance process.…”
Section: Introductionmentioning
confidence: 79%
“…Among some of the top reasons that people decided to leave their groups was because of legal problems, being injured, and being burned out with the lifestyle. Bullard & Reid (2019) and Pyrooz et al (2017) found in their work that one of the best times to pull gang members out of their groups was during critical moments (e.g., during emergency services) when they have been seriously injured or have faced some major negative life consequence in some way (e.g., being stabbed, jumped). The decision to leave the group often results from a combination of pushes and pulls (Berger et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Macfarlane (2018) pointed out that social factors play a major role in placing people at-risk of joining deviant groups, such as negative peer relations and coming from a dysfunctional family environment. In relation to this, Pyrooz, McGloin, & Decker (2017) found in their research that poor parenting and the intergenerational transmission of gang identity often plays a major role when it comes to a young person becoming involved with a gang.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations